2017
DOI: 10.7860/jcdr/2017/28750.10475
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study of ER, PR, Ki67 and p53 in Endometrial Hyperplasias and Endometrial Carcinomas

Abstract: Introduction: Endometrial carcinoma is the second most common gynecologic malignancy in the developing countries. Endometrial Hyperplasia (EH) is a precursor to Endometrioid Adenocarcinoma (EMAC). A 23% of Atypical Hyperplasias (AEH) progress to EMAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
0
14
0
2
Order By: Relevance
“…In our study 100% of the cases of endometrial carcinoma showed positive expression of ER. However studies by Suthipintawong et al; [23] Suamchock et al; [24] Markova et al; [25] Sidonia et al; [26] Yu CG et al; [27] Pasam et al; [28] Musfera et al 29] ER expression was present in 76%, 59.3%, 79.3%,86.3%,44.7%, 68% and 60.7% of the cases respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In our study 100% of the cases of endometrial carcinoma showed positive expression of ER. However studies by Suthipintawong et al; [23] Suamchock et al; [24] Markova et al; [25] Sidonia et al; [26] Yu CG et al; [27] Pasam et al; [28] Musfera et al 29] ER expression was present in 76%, 59.3%, 79.3%,86.3%,44.7%, 68% and 60.7% of the cases respectively.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR protein is normally expressed in normal glandular endometrium, and EGFR could play a dual role in endometrial carcinoma, such that high EGFR expression in type I carcinoma is associated with low grade and favorable outcomes, but in contrast, EGFR expression in type II carcinoma was associated with high grade and adverse clinical outcome. (14)(15)(16)(17) The p53 mutation in endometrial carcinoma is related to tumor survival and metastasis risk, (18) however, in the endometrioid adenocarcinoma it was observed p53 immunostaining only in papillary area of the tumor. At the present investigation in clear cells RCC p53 expression was negative ( Figure 2), but nevertheless p53 expression is considered rare in clear cells RCC, in relation to other types of renal carcinomas.…”
Section: Discussionmentioning
confidence: 98%
“…For ki67 and p53 staining assessment, nuclear staining intensity was scored using three categories; mild, moderate, and strong. e staining ratio was scored as 0 for no staining, 1 for <10%, 2 for 10% to 50%, and 3 for >50% [13].…”
Section: Staining Scoringmentioning
confidence: 99%
“…ey describe a pattern which is not seen in normal tissue and is different from diffuse p16 positivity as seen in high-risk HPV positive cervical intraepithelial lesions [11]. Inoue [12] reported that endometrial metaplasia, in general, was a precursor of variant types of endometrial carcinomas, based on the p53, PCNA, and ki67 overexpression in EC and endometrial metaplasia and the fact that EC are often accompanied by adjacent metaplastic epithelium [13]. However, it is, for now, not a generally accepted view that endometrial metaplasia is a precursor of endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%